2020
DOI: 10.3389/fncel.2020.00023
|View full text |Cite|
|
Sign up to set email alerts
|

IRSp53 Deletion in Glutamatergic and GABAergic Neurons and in Male and Female Mice Leads to Distinct Electrophysiological and Behavioral Phenotypes

Abstract: IRSp53 (also known as BAIAP2) is an abundant excitatory postsynaptic scaffolding protein implicated in autism spectrum disorders (ASD), schizophrenia, and attention-deficit/hyperactivity disorder (ADHD). IRSp53 is expressed in different cell types across different brain regions, although it remains unclear how IRSp53 deletion in different cell types affects brain functions and behaviors in mice. Here, we deleted IRSp53 in excitatory and inhibitory neurons in mice and compared resulting phenotypes in males and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 68 publications
3
27
3
Order By: Relevance
“…Here, we provide an in vivo example of this concept by demonstrating that IRSp53-KO mPFC excitatory neurons show increased spontaneous firing activity but a limited firing-rate range during social and non-social cue exploration. The heightened firing rates of mPFC pExc neurons in IRSp53-KO mice during the rest period may be attributable to the increased intrinsic excitability of pyramidal mPFC neurons, as reported in IRSp53-KO mice with gene deletion restricted to excitatory neurons (Kim et al, 2020). An elevated firing rate at rest was observed for mPFC neurons in socially impaired Cntnap2-KO mice; this was .…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Here, we provide an in vivo example of this concept by demonstrating that IRSp53-KO mPFC excitatory neurons show increased spontaneous firing activity but a limited firing-rate range during social and non-social cue exploration. The heightened firing rates of mPFC pExc neurons in IRSp53-KO mice during the rest period may be attributable to the increased intrinsic excitability of pyramidal mPFC neurons, as reported in IRSp53-KO mice with gene deletion restricted to excitatory neurons (Kim et al, 2020). An elevated firing rate at rest was observed for mPFC neurons in socially impaired Cntnap2-KO mice; this was .…”
Section: Discussionmentioning
confidence: 65%
“…The heightened firing rates of mPFC pExc neurons in IRSp53-KO mice during the rest period may be attributable to the increased intrinsic excitability of pyramidal mPFC neurons, as reported in IRSp53-KO mice with gene deletion restricted to excitatory neurons (Kim et al, 2020). An elevated firing rate at rest was observed for mPFC neurons in socially impaired Cntnap2-KO mice; this was is the firing rate at the target zones.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Studies have shown that IRSp53 is involved in various brain disorders, including ASD [98,99], attention deficit hyperactivity disorder [100] and schizophrenia [101]. A deletion of Irsp53 leads to sexdependent changes in behaviour, such as social deficit, hyperreactivity and excitatory/inhibitory imbalance [102]. A lack of IRSp53 activity leads to NMDA receptor hyperreactivity in the hippocampus [103] and prepulse inhibition in cortical excitatory neurons [102].…”
Section: Shank Family Of Genesmentioning
confidence: 99%
“…In contrast, in the medial prefrontal cortex (mPFC), IRSp53 −/− mice show a decrease in frequency and amplitude of mEPSCs and synapse numbers by EM without affecting NMDA receptor function (Chung et al, 2015 ). Deletion of IRSp53 in glutamatergic neurons and GABAergic mPFC neurons lead to distinct behavioral deficits and synaptic changes between male and female mice (Kim et al, 2020 ). Whether these differences reflect alterations at the synaptic or circuit level or reflect compensation by other I-BAR proteins is not yet clear.…”
Section: Introductionmentioning
confidence: 99%